A Design of a 345-kV Electric Power Transmission Line Interlinking Ramu and Rouna Grids in Papua New Guinea - Francis, Sakato; Joseph, Fisher; Hoole, P.R.P; Martin, Anyi; Hoole, S.R.H. (EDP Sciences, 2017)
According to PNG Power Limited (PPL), Papua New Guinea’s peak power demand is expected to increase from 210 MW in 2012 to 347 MW in 2026. Under the current state of the power sector in Papua New Guinea (PNG), it is critical to implement measures to cope with the increasing power demand to promote investment, economic growth, and ultimately to achieve poverty reduction through economic growth. One of the solutions identified to improve the reliability of PNG power systems and thus to meet the demand is to interconnect the major grids in the country so that the loads could be shared among them. This project embarks in designing a 345-kV electric power transmission line to interlink the Ramu and Rouna power grids of Papua New Guinea. The design is done by analysing all the necessary aspects of the transmission lines with in-depth calculations performed using MATHCAD software. This design is the basis for extra-high voltage (EHV) transmission network in anticipation for the power generation and demand growth in PNG.